A novel nanocomposite based on covalent organic polymer and nanocellulose for thin‐film microextraction of imipramine from biological samples. Issue 15 (10th June 2021) - Dowlatshah, Samira; Saraji, Mohammad; Dinari, Mohammad; Soltani, Roozbeh
Abstract: A novel covalent organic polymer was prepared using 1, 5‐diaminonaphthalene as a linker and cyanuric chloride as a node. A thin‐film nanocomposite of 1, 5‐diaminonaphthalene covalent organic polymer and cellulose nanocrystalline was then fabricated via filtering and casting method. The effect of incorporation of various amounts of 1, 5‐diaminonaphthalene covalent organic polymer and cellulose nanocrystalline was studied to obtain an efficient nanocomposite thin‐film with a large number of polar functional groups and high mechanical stability. Field emission scanning electron microscopy, X‐ray diffraction, Fourier transform infrared spectrometry, and thermogravimetric analysis techniques were applied for the characterization of physicochemical properties of the prepared materials. Imipramine was determined in the biological samples using thin‐film microextraction followed by gas chromatography flame ionization detection. Parameters affecting the extraction efficiency of imipramine were investigated. Under the optimized conditions, the limit of detection was 0.5 ng/mL. Film‐to‐film reproducibility for three different films fabricated under the same conditions (at three concentration levels) varied between 8.9 and 9.7%. The linear dynamic range covered more than three orders of magnitude (2–5000 ng/mL) with a determination coefficient of 0.9985. The method was successfully applied for preconcentration and determination of imipramine in biological samples with spiking recoveries between 78 and 93%.